Developments in Long Span Composite Slabs - Widjaja, Budi R.; Easterling, W. Samuel (Engineering Journal, 2000)
Composite slabs constructed using cold-formed steel deck are by far the most common forms of floor used in steel-framed buildings in the United States. Indeed it is largely due to the attributes that steel deck provides that make steel-framed buildings as economically competitive as they are. The maximum unshored span, using composite deck profiles manufactured in the U.S., is approximately 15 ft. However, the use of 16 ga deck and lightweight concrete is required to achieve 15 ft unshored clear spans. This number depends on the deck cross section as well as the concrete thickness and unit weight. Typically, deck spans in the range of 8-10 ft are used. The choice of unshored construction is common because of the savings in construction cost and time. If the typical span lengths can be increased by a factor of say 1.5 to 2, significant cost savings can be expected because of the reduction in the number of filler beams and their connections to the girders. The cost of the steel deck will increase, however the savings realized by using fewer filler beams will be greater than this increase. The advantage stems largely from cost savings in fabrication and erection of fewer members and connection of those members.